Defining a dichotomous indicator for population-level assessment of dietary diversity among pregnant adolescent girls and women: A secondary analysis of quantitative 24-h recalls from rural settings in Bangladesh, Burkina Faso, India, and Nepal - Verger, Eric O.; Eymard-Duvernay, Sabrina; Bahya-Batinda, Dang; Hanley-Cook, Giles T.; Argaw, Alemayehu; Becquey, Elodie; Diop, Loty; Gelli, Aulo; Harris-Fry, Helen; Kachwaha, Shivani; Kim, Sunny S.; Nguyen, Phuong Hong; et al. (Elsevier, 2024)
Background The Minimum Dietary Diversity for Women of Reproductive Age (MDD-W) indicator was validated as a proxy of micronutrient adequacy among nonpregnant women in low- and middle-income countries (LMICs). At that time, indeed, there was insufficient data to validate the indicator among pregnant women, who face higher micronutrient requirements. Objective This study aimed to validate a minimum food group consumption threshold, out of the 10 food groups used to construct MDD-W, to be used as a population-level indicator of higher micronutrient adequacy among pregnant women aged 15–49 y in LMICs. Methods We used secondary quantitative 24-h recall data from 6 surveys in 4 LMICs (Bangladesh, Burkina Faso, India, and Nepal, total n = 4909). We computed the 10-food group Women's Dietary Diversity Score (WDDS-10) and calculated the mean probability of adequacy (MPA) of 11 micronutrients. Linear regression models were fitted to assess the associations between WDDS-10 and MPA. Sensitivity, specificity, and proportion of individuals correctly classified were used to assess the performance of MDD-W in predicting an MPA of >0.60. Results In the pooled sample, median values (interquartile range) of WDDS-10 and MPA were 3 (1) and 0.20 (0.34), respectively, whereas the proportion of pregnant women with an MPA of >0.60 was 9.6%. The WDDS-10 was significantly positively associated with MPA in each survey. Although the acceptable food group consumption threshold varied between 4 and 6 food groups across surveys, the threshold of 5 showed the highest performance in the pooled sample with good sensitivity (62%), very good specificity (81%), and percentage of correctly classified individuals (79%). Conclusions The WDDS-10 is a good predictor of dietary micronutrient adequacy among pregnant women aged 15–49 y in LMICs. Moreover, the threshold of 5 or more food groups for the MDD-W indicator may be extended to all women of reproductive age, regardless of their physiologic status.